Outcomes and Complications of Wright Medical INVISION Talus for Complex Total Ankle Arthroplasty - Yvonne C. Conway MD; Spenser Cassinelli MD; Scott Whitlow MD; Gregory A. Lundeen MD, MPH (Foot & Ankle Orthopaedics)
Category: Ankle Arthritis; Ankle Introduction/Purpose: The INVISION Total Ankle Arthroplasty System (Wright Medical Technology/Stryker) is a modular ankle arthroplasty used for patients with limited bone stock. There is limited early survivorship and clinical outcomes data for this device. The aim of this study is to report on early implant survivorship and complications specifically with regards to the talar component of the INVISION Total Ankle System performed in complex and revision total ankle replacements. Methods: This is a single-institution retrospective review of patients who underwent TAA using the INVISION talus implant between 2018 and 2023. INVISION was chosen in cases with significant talar bone loss. Demographics, reoperation, complications, and radiographic data were collected. Immediate postoperative images were used to measure the height of bone remaining underneath the talar tray at the thinnest remaining portion of the posterior talus. A total of 8 components in 7 different patients that underwent INVISION talar component placement met inclusion criteria with a mean follow-up of 105 weeks. Patient demographics consisted of 71% female(n=5), 29% male(n=2) with mean age of 56 years old. The INVISION talar component was used as a primary implant to address severe AVN of the talus (n= 3), and as a revision talar component to address post infection bone loss (n= 3) and failed total ankle arthroplasty due to aseptic loosening/osteolysis/subsidence (n = 2). Results: Talar implant survivorship was 88%. One patient had implant failure resulting in conversion to a total talus due to loss of fixation of the talar component. Another patient developed a stress fracture 2 years postoperatively in the posterior talus (Figure 1.C) that was successfully treated with a subtalar fusion. The average measured minimum posterior talus thickness underneath the tray for all patients was 4.6mm (range 0.5mm – 10.0 mm). This measurement was not able to be obtained for one patient with a prior subtalar fusion due to talar continuity with calcaneus. In the two patients that had either implant failure or required reoperation, the talar thickness measured 0.5mm and 2.9mm, respectively. None of the implants with greater than 3mm had loss of fixation or ingrowth. Conclusion: The INVISION talus tray is a reliable option for addressing severe talar bone loss in TAA. We caution surgeons using this implant if there is < 3 mm of bone height in the posterior talus. Although the pegs of the talar plate are primarily fixated anterior within the talus, the tray appears to rely on the entire length of the talus to distribute the weightbearing forces. If a surgeon measures >3mm posterior talar height underneath the talar plate, alternative treatments such as subtalar fusion in conjunction with the INVISION talar component placement or total talus should be considered.